2001
DOI: 10.1073/pnas.091101898
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic dissection of dome formation in a mammary cell line: Role of tropomyosin-5b and maspin

Abstract: In this work we extended the study of genes controlling the formation of specific differentiation structures called ''domes'' formed by the rat mammary adenocarcinoma cell line LA7 under the influence of DMSO. We have reported previously that an interferon-inducible gene, rat-8, and the ␤-subunit of the epithelial sodium channel (ENaC) play a fundamental role in this process. Now, we used a proteomic approach to identify proteins differentially expressed either in DMSO-induced LA7 or in 106A10 cells. Two diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
27
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…A subclone of LA7AA10 cells, LA73F12ms (which we designate as stem LA7 [sLA7]) cells have the ability, at the single-cell level, to generate branched ductal-alveolar-like structures in three-dimensional (3D) cultures that morphologically and functionally recapitulate the tubuloalveolar architecture of the mammary tree. Exposure of sLA7 cells to lactogenic hormones, lipids, or differentiating agents (e.g., DMSO) results in the formation of dome-shaped structures representing the cellular changes that occur in the mammary gland at pregnancy, when alveoli are formed (9)(10)(11)(12)(13)(14)(15)(16). sLA7 cells express CD29 and CD49f, which mark a mammary stem cell-enriched population in mice (17)(18)(19), as well as CD44 and CD133, which are markers for breast, colon, prostate, and pancreatic CSCs and brainstem cells (5)(6)(7)(8)(20)(21)(22)(23), and p21/ WAF1 , which is a gene involved in the maintenance of the quiescence of mammary, hematopoietic, and brain stem cells (24)(25)(26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A subclone of LA7AA10 cells, LA73F12ms (which we designate as stem LA7 [sLA7]) cells have the ability, at the single-cell level, to generate branched ductal-alveolar-like structures in three-dimensional (3D) cultures that morphologically and functionally recapitulate the tubuloalveolar architecture of the mammary tree. Exposure of sLA7 cells to lactogenic hormones, lipids, or differentiating agents (e.g., DMSO) results in the formation of dome-shaped structures representing the cellular changes that occur in the mammary gland at pregnancy, when alveoli are formed (9)(10)(11)(12)(13)(14)(15)(16). sLA7 cells express CD29 and CD49f, which mark a mammary stem cell-enriched population in mice (17)(18)(19), as well as CD44 and CD133, which are markers for breast, colon, prostate, and pancreatic CSCs and brainstem cells (5)(6)(7)(8)(20)(21)(22)(23), and p21/ WAF1 , which is a gene involved in the maintenance of the quiescence of mammary, hematopoietic, and brain stem cells (24)(25)(26).…”
mentioning
confidence: 99%
“…We have used LA7AA10 cells, isolated by Dulbecco from a mammary adenocarcinoma induced in rat by dimethylbenzanthracene to study mammary gland differentiation (9)(10)(11)(12)(13)(14)(15)(16) and, more recently, as a potential CSC model (17). A subclone of LA7AA10 cells, LA73F12ms (which we designate as stem LA7 [sLA7]) cells have the ability, at the single-cell level, to generate branched ductal-alveolar-like structures in three-dimensional (3D) cultures that morphologically and functionally recapitulate the tubuloalveolar architecture of the mammary tree.…”
mentioning
confidence: 99%
“…The identification of genes involved in the process of dome formation has been the focus of our previous studies, carried out by using a differential expression detection approach (cDNA library subtraction) and proteomics-based technologies (8,14,(16)(17)(18). This work has shown that the differentiation process resulting in the formation of domes requires the expression of the rat8 gene and the ␤-subunit of the amiloride-sensitive epithelial sodium channel (ENaC) and is negatively regulated by genes coding YMP (Y membrane protein) and maspin (8,14,16,17). rat8 is the key gene regulating dome formation; rat8 is constitutively expressed in LA7, but not in 106, cells and moderately induced by DMSO treatment in both cell lines (8).…”
mentioning
confidence: 99%
“…and R.D., unpublished observations). By differential cloning of genes, using subtractive cDNA library construction and proteomic-based technologies, both performed on DMSO-induced LA7 and 106 cells, we determined that dome formation in LA7 cells is under strict gene regulation (16)(17)(18). Among the genes we identified differentially expressed between the two cell lines, we demonstrated to be critical in dome formation: rat8, tropomyosin-5B, maspin, the ␤ subunit of the epithelial sodium channel, and the rat homolog of the human EMP3 gene.…”
mentioning
confidence: 99%
“…WDMN1, originally identified as a gene whose expression is diminished in metastatic rat mammary adenocarcinomas, is a member of a family of protease inhibitors and encodes a secreted protein that may inhibit metastases by inhibiting proteases (19)(20)(21). WDNM1 and ␤-casein genes appear to be specific markers of mammary gland functional differentiation because in vivo the expression of these two genes occurs earlier in pregnancy (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), suggesting that their expression in LA7 cells may be indicative of a possible relationship between the biological processes resulting in dome formation in vitro and the processes resulting in the alveoli differentiation of the mammary gland at pregnancy.…”
mentioning
confidence: 99%